Augmentation of phosphate-induced osteo-/chondrogenic transformation of vascular smooth muscle cells by homoarginine - Alesutan, Ioana Simona; März, Winfried (Cardiovascular research, 2016)
Aims: Reduced homoarginine plasma levels are associated with unfavourable cardiovascular outcome in chronic kidney disease (CKD). Cardiovascular events in CKD are fostered by vascular calcification, an active process promoted by hyperphosphatemia and involving osteo-/chondrogenic transformation of vascular smooth muscle cells (VSMCs). The present study explored the effect of homoarginine on phosphate-induced osteo-/chondrogenic signalling and vascular calcification. Methods and results: Experiments were performed in hyperphosphatemic klotho-hypomorphic mice (kl/kl), in subtotal nephrectomy and vitamin D3–overload mouse calcification models and in primary human aortic smooth muscle cells (HAoSMCs). As a result, plasma homoarginine levels were lower in kl/kl mice than in wild-type mice and in both genotypes significantly increased by lifelong treatment with homoarginine. Surprisingly, homoarginine treatment of kl/kl mice and of mice with renal failure after subtotal nephrectomy augmented vascular calcification and enhanced the transcript levels of plasminogen activator inhibitor 1 (Pai1) and of osteogenic markers Msx2, Cbfa1, and Alpl. Similarly, homoarginine treatment of HAoSMCs increased phosphate-induced calcium deposition, ALP activity, as well as PAI1, MSX2, CBFA1, and ALPL mRNA levels. Homoarginine alone up-regulated osteo-/chondrogenic signalling and indicators of oxidative stress in HAoSMCs. Furthermore, homoarginine reduced citrulline formation from arginine by nitric oxide (NO) synthase (NOS) isoforms. NO formation by NOS was reduced when using homoarginine as a substrate instead of arginine. The osteoinductive effects of homoarginine were mimicked by NOS inhibitor L-NAME and abolished by additional treatment with the NO donors DETA-NONOate and PAPA-NONOate or the antioxidants TEMPOL and TIRON. Furthermore, homoarginine augmented vascular calcification and aortic osteo-/chondrogenic signalling in mice after vitamin D3-overload, effects reversed by the NO donor molsidomine. Conclusion: Homoarginine augments osteo-/chondrogenic transformation of VSMCs and vascular calcification, effects involving impaired NO formation from homoarginine.